The Nature of Local Place Branding Strategies: The Cases of Almaty (KZ), Belo Horizonte (BR) and Wroclaw (PL) - Sztando, Andrzej; Moreira Silva, João Paulo; Kazybayeva, Aizhan (Charakter lokalnych strategii marketingu miejsc: Studium przypadków Ałmatów (KZ), Belo Horizonte (BR) i Wrocławia (PL), 2024)
Aim: The aim of the research was to identify and evaluate the features of place marketing strategies of Almaty (Kazakhstan), Belo Horizonte (Brazil) and Wroclaw (Poland), as methods of stimulating sustainable economic development. Methodology: The research employed a comparative case study methodology. Results: The research showed that although all the place marketing strategies studied are aimed at stimulating local economic processes, they lack features that ensure the sustainability of these processes. Implications and recommendations: The results indicate limitations and tensions in the area of place branding strategies in the scope of their impact on sustainable economic development thus motivate representative research and the search for more sustainable solutions. Originality/value: The literature query did not reveal any previous examples of such research, and the methodology was partly original. The article provides new information on the place marketing strategies used in different countries and evaluate them in relation to the paradigm of sustainable development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2024; vol. 68, nr 4, s. 86-99
Keywords: place marketing strategy; sustainable economic development; Almaty; Belo Horizonte; Wroclaw; strategia marketingu miejsca; zrównoważony rozwój gospodarczy; Ałmaty; Wrocław